EDUCANDO COM CONSCIÊNCIA - Daniela Queiroz (Universidade Federal Fluminense (UFF), 2017)
Resenha do Livro: LOUREIRO, Carlos Frederico; TORRES, Juliana Rezende (orgs.). Educação Ambiental - dialogando com Paulo Freire. São Paulo: Cortez, 2014. 184p.